Perbandingan Dua Desinfektan dalam Mengeliminasi Virus Avian Influenza H5N1 pada Telur Tetas - Umar Suryanaga; Retno D. Soejoedono; Ni Luh Putu Ika Mayasari (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Avian Influenza (AI) is a zoonotic viral disease in birds which demands priority on control and measures. Spread of AI virus can occur directly or indirectly. The use of disinfectant and handling of hatching egg waste into one of the actions that must be applied in hatchery to control the spread of AI virus. This research aim to compared two types of desinfectant in eliminating AI virus. The research was designed into 6 groups. Group I was SAN (Specific Antibody Negative) eggs as untreated negative control, group II was SAN egg treated by fumigation using potassium permanganate (KMnO4) and formalin in room temperature for 20 minutes, group III was SAN eggs soaked in benzalkolnium chloride (BKC) in room temperature for 30 seconds, group IV was SAN contaminated by AI H5N1 virus and fumigated by potassium permanganate and formalin in room temperature for 20 minutes, group V was SAN eggs contaminated by AI H5N1 virus and then soaked in benzalkonium chloride in room temperature for 30 second, and group VI was SAN eggs contaminated by AI H5N1 virus in room temperature for 10 minutes as positive control. AI H5N1 virus detection was done by using RT-PCR (Reverse Transcription Polymerase Chain Reaction) and confirmed by isolation in Embyronated Chicken Egg. The result of this research showed that the use of potassium permanganate and formalin disinfectant gave little better performance compared to benzalkoniun chloride in eliminating AI H5N1 virus on hatching eggs.